Association of Fetal Atrial Flutter with Neonatal Atrioventricular Re-entry Tachycardia Involving Accessory Pathway: A Link to be Remembered - Michael Lewis (Pediatric Cardiology, 2021)
To investigate prenatal and postnatal outcomes of atrial flutter and its association with the development of a second tachycardia, following restoration of sinus rhythm, in the fetus or newborn. This study is a retrospective review of all fetuses that presented with atrial flutter from January 2001 to December 2019 at the University Hospital of Wales, Cardiff, UK. The specific type of arrhythmia, its time of appearance and clinical characteristics, echocardiographic findings, medical management, and postnatal outcomes were evaluated. Sixteen fetuses were diagnosed with atrial flutter (AFL). Thirteen fetuses had persistent AFL and three fetuses had intermittent AFL. Seven patients had hydrops, of which one had Ebstein’s anomaly and the other six had normal hearts. Three of the fetuses that presented with AFL were diagnosed at 20, 21, and 23 weeks’ gestation and the remainder were diagnosed in the third trimester. Thirteen patients with AFL received antiarrhythmic drugs and three were delivered without any treatment. Five fetuses with AFL developed atrioventricular reciprocating tachycardia following DC cardioversion after birth, and four of them exhibited pre-excitation on the ECG. These five patients (31.3%) required postnatal antiarrhythmic treatment for up to 2 years. Pre-excitation disappeared in two patients during follow-up and two asymptomatic patients with neonatal pre-excitation required accessory pathway ablation. Fetal atrial flutter has a strong association with atrioventricular reciprocating tachycardia and ventricular pre-excitation in the neonatal period. Therefore, electrocardiograms should be carefully reviewed in newborns following the initial resolution of atrial flutter.